Identification and Validation of a Novel Immune-Related lncRNA Signature for Bladder Cancer - Hua, Shan; Xie, Zhiwen; Wang, Wenhao; Wan, Zhong; Chen, Min; Zhao, Sheng; Jiang, Juntao (Frontiers in Oncology, 2021)
Purpose: We aimed to construct an immune-related long noncoding ribonucleic acids (irlncRNA) signature to evaluate the prognosis of patients without specific expression level of these irlncRNA. Methods: The raw transcriptome data were downloaded from The Cancer Genome Atlas (TCGA), irlncRNAs were filtered out using an online immune related gene database and coexpression analysis, differently expressed irlncRNA (DEirlncRNA) pairs were identified by univariate analysis. The areas under curve (AUC) were compared and the Akaike information criterion (AIC) values of receiver operating curve (ROC) was counted, the most optimal model was constructed to divide bladder cancer patients into high- and low-risk groups using the cut-off point of ROC. Then, we evaluated them from multiple perspectives, such as survival time, clinic-pathological characteristics, immune-related cells infiltrating, chemotherapeutics efficacy and immune checkpoint inhibitors. Results: 14 DEirlncRNA pairs were included in this signature. Patients in high-risk groups demonstrated apparent shorter survival time, more aggressive clinic-pathological characteristics, different immune-related cells infiltrating status, lower chemotherapeutics efficacy. Conclusion: The irlncRNA signature demonstrated a promising prediction value for bladder cancer patients and was important in guiding clinical treatment.